2016
DOI: 10.1002/bit.26189
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes involved in polysaccharide bioflocculant synthesis in Bacillus licheniformis

Abstract: The present study reports the sequenced genome of Bacillus licheniformis CGMCC 2876, which is composed of a 4,284,461 bp chromosome that contains 4,188 protein-coding genes, 72 tRNA genes, and 21 rRNA genes. Additional analysis revealed an eps gene cluster with 16 open reading frames. Conserved Domains Database analysis combined with qPCR experiments indicated that all genes in this cluster were involved in polysaccharide bioflocculant synthesis. Phosphoglucomutase and UDP-glucose pyrophosphorylase were suppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…In our previous studies, B . licheniformis CGMCC2876 was observed to produce extracellular polysaccharides when using glucose as the sole carbon source [ 13 , 14 ], whereas poly-γ-glutamic acid (γ-PGA) was secreted when trisodium citrate and glycerol were used as the carbon sources [ 15 ]. Both of the extracellular polymeric substances exhibited high flocculating activities.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, B . licheniformis CGMCC2876 was observed to produce extracellular polysaccharides when using glucose as the sole carbon source [ 13 , 14 ], whereas poly-γ-glutamic acid (γ-PGA) was secreted when trisodium citrate and glycerol were used as the carbon sources [ 15 ]. Both of the extracellular polymeric substances exhibited high flocculating activities.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that EpsB contained the structural domain of the tyrosine kinase CpsD, which had a negative regulatory role on the formation of capsular polysaccharides in Streptococcus aureus [ 15 ] according to an analysis of the NCBI Conserved Domains. Therefore, we inferred that epsB had a negative regulatory effect on the synthesis of polysaccharides in B. licheniformis and thereby decreased the flocculating activity [ 11 ]. However, although the most recent results showed that overexpressing epsB indeed decreased the polysaccharide content synthesized by B. licheniformis , the flocculating activity of the bioflocculant was greatly improved compared with that of the original strain because overexpressing epsB produced a marked increase in the γ-PGA content.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research, a bioflocculant-producing bacterium was isolated and identified as B. licheniformis [China General Microbiological Culture Collection Centre (CGMCC) 2876] [ 10 ], and it could produce polysaccharide and γ-PGA under different culture conditions. When using glucose as the sole carbon source, B. licheniformis mainly produces extracellular polysaccharides [ 11 ], whereas when using trisodium citrate and glycerol as the carbon sources, this strain mainly secretes γ-PGA [ 12 ]. Both polysaccharides and γ-PGA have shown high flocculating activities in industrial applications, so the ability to increase the flocculating activities of bioflocculants produced by B. licheniformis has huge commercial potential [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations